Perancangan Sistem Informasi Pendataan Dan Penggajian Karyawan Sekretariat Mpu Kota Lhokseumawe Berbasis Web - Munar, Munar; Nisa, Khairun (Jurnal Tika, 2022)
The system for designing information on data collection and payroll for employees of the Lhokseumawe MPU secretariat is an online-based computerized data processing system, namely in the form of a website, this system can be opened on internet media which can be accessed by users and admins. In designing an information system, employee data can be divided into two, namely user access rights which include employee information, overtime information, fourm information, activity information, and absence information. Meanwhile, admin information is only for processing employee data, absence data, salary data, overtime data, and printing reports. To process employee data using the website system, Xampp 17.4 and Macromedia Dreamweaver programming is required. So to make the system required javascript language, php, htm, and css. The design results are in the form of employee reports, attendance reports, salary reports, and overtime reports